Increased Motivation and Ability Student Numeracy Through the Application of a Contextual Approach to Mathematics Learning - Rahayu, Wiwin Noviyati; Firdaus , Fery Muhamad (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
This research aims to describe and analyze: 1) the implementation of a contextual approach to mathematics learning in perimeter of plane figures material to increase the motivation and numeracy skills of third-grade students at Cawan Jatinom Klaten Elementary School, 2) the increase in students' learning motivation after implementing the contextual approach, and 3) the improvement in students' numeracy skills following its application. The research employed a Classroom Action Research (CAR) design, comprising planning, implementation, observation, and reflection. The subjects consisted of 12 third-grade students, and data were collected through tests, observations, interviews, and documentation. Data analysis was conducted using both quantitative and qualitative methods. The results showed that the contextual learning approach, implemented through the use of measuring tapes and real objects inside and outside the classroom, successfully increased students' engagement and understanding of perimeter concepts. Students became more active and motivated; the classroom atmosphere became more conducive to learning, and instruction shifted from a teacher-centred to a student-centred approach. After two cycles of intervention, students' numeracy skills improved, as the hands-on use of real objects helped them grasp concepts such as length, width, and circumference more easily. It is recommended that the contextual learning approach be applied in other classes or explored further to enhance mathematics teaching methods in general.